2000
DOI: 10.1152/jappl.2000.88.4.1291
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of elastomer arterial models with specified compliance

Abstract: A simple way of making elastic tubes using a mechanical lathe for precise control of the wall thickness is proposed in this study. These tubes are particularly useful for modeling properties of large arteries. Tubes with different geometric parameters and hence different elastic behavior have been made with a silicon elastomer (Rhodorsil RTV 1556). They have been created to be used for compliance measurements in hemodynamics research. Within a limited range of pressures, depending on the wall thickness, such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…1. A similar tendency was observed by Stevanov et al (2000) who showed the measured vessel compliance at 1.04 mm wall thickness was 12.3% lower than the predicted value.…”
Section: Determination Of Compliancesupporting
confidence: 86%
See 1 more Smart Citation
“…1. A similar tendency was observed by Stevanov et al (2000) who showed the measured vessel compliance at 1.04 mm wall thickness was 12.3% lower than the predicted value.…”
Section: Determination Of Compliancesupporting
confidence: 86%
“…At higher values of the pressure p, a deviation from the linear trend is detected. Stevanov et al (2000) found a value of 80 mmHg at a wall thickness of 1.04 mm, up to which the dilatation was linear. These authors also realized the critical pressure level to increase with wall thickness, such that the present finding is consistent with their conclusion.…”
Section: Determination Of Compliancementioning
confidence: 90%
“…8,19 This technique gives a reliable index of the regional AoStiff, 28,29 but represents only an estimate of the local AoStiff because it is a summation of the individual biomechanical properties of different arterial walls (that is, carotid, aorta, iliac and femoral arteries) located between the two recording sites. 30,31 Our data showed that IWV measurements are highly correlated with the carotid-femoral PWV, indicating that IWV also provides a reliable estimate of the regional AoStiff (see Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 56%
“…Different materials are available for manufacturing rigid models [4,8], typically for the purpose of carrying out visualization studies, for example, particle image velocimetry [9]. However, rigid models do not replicate the compliant properties of the vasculature.Flexible elastomer arterial models with varying wall thickness have been used for investigating hemodynamics of the aortic circulation [10,11], but a realistic compliant model of the pulmonary arteries has not been presented. In this study, we describe the manufacturing of a compliant pulmonary arterial model based on patient anatomy created with rapid prototyping.…”
mentioning
confidence: 99%